The structural characteristics of the lifestyle among older adults and its impact on the health in China - Wang, Xiaohui; Miao, Haimin; Jin, Qiaosen (Frontiers in Public Health, 2023)
Objective: Enhancing overall health remains a primary global objective, with lifestyle being a crucial factor impacting elderly health status. This study focuses on the lifestyles of Chinese elderly, systematically exploring the evolution and characteristics of their lifestyle and investigating its impact on their health. Methods: Utilizing panel data from the Chinese Longitudinal Health Longevity Survey (CLHLS)from 2008, 2011, 2014, and 2018, we adopted 15 indicators reflecting elderly lifestyle. Latent class analysis and ordinary least square regression were used to uncover the structural nuances of the Chinese elderly lifestyle and its effects on health. Results: The study identifies three distinct lifestyle categories for the elderly: relatively positive, mixed, and relatively negative. It reveals that the Chinese elderly do not predominantly adopt a positive lifestyle, and this trend persisted from 2008 to 2018. Each improvement in lifestyle category significantly boosts the elderly's physical health, mental health, and self-assessed health by 11.2%, 3.6%, and 17.1% respectively. Conclusions: To attain the strategic aim of healthy aging, efforts should prioritize encouraging the elderly to adopt a positive lifestyle, enhance the geriatric health service system, and promote an intelligent lifestyle management model.